Early drain removal after hepatectomy: an underutilized management strategy. Issue 10 (October 2020) - Fagenson, Alexander M.; Gleeson, Elizabeth M.; Lau, Kelvin K.N.; Karachristos, Andreas; Pitt, Henry A.
Abstract: Background: Recent data suggest that routine drainage is unnecessary in patients undergoing hepatectomy, but many surgeons continue to utilize drains. We compared the outcomes of patients undergoing early versus routine drain removal after hepatectomy. Methods: Patients having drains placed during major (≥3 segments) or partial hepatectomy (≤2 segments) were identified in the 2014-16 ACS-NSQIP database. Propensity matching between early (POD 0–3) and routine (POD 4–7) drain removal and multivariable regressions were performed. Results: Early drain removal was performed in 661 (40%) of patients undergoing a partial hepatectomy and 211 (22%) of major hepatectomy patients. After matching, 719 early and 719 routine drain removal patients were compared. Early drain removal patients had lower overall (12 vs 19%, p < 0.001) and serious (9 vs 13%, p < 0.03) morbidity as well as fewer bile leaks (2.1% vs 5.0%, p < 0.003). Length of stay was two days shorter (4 vs 6 days, p < 0.01) and readmissions were less frequent (5.4 vs 8.1%, p = 0.02) for patients undergoing early drain removal. Conclusion: Early drain removal is associated with fewer overall and serious complications, shorter length of stay and fewer readmissions. Early drain removal after hepatectomy is an underutilized management strategy.